“Niveles de fertilización nitrogenada en suelo seco sobre el rendimiento de arroz (oryza sativa L.), al transplante, en el bajo mayo” - Arévalo Cárdenas, Celso Nazario (2001)
The main objective of the thesis was to determine the effect of the íncorporation of different nitrogen levels (formulated in urea) in dry soil in the yield of rice shell and quality of grain of the variety Capirona, in transplant system in the Estación Experimental "El Porvenir" San Martín, Peru. The design experimental employed was at random of Complete Blocks with five treatments and four repetitions. The fertilization and nitrogen incorporation went to the volley, in dry soil, 50% before the transplant and the other 50% in the period of cotton point (80 DDS). The treatment T 3, ( Incorporation of 50% of the <lose to the volley in dry soil, before the transplant and 50% in the period of cotton point )reached the biggest grain yield with 8 693 Kg./ha, overcoming the witness that showed precocity to the flowering in front of the other treatments significantly. The treatments T 3 and T 2 ( Incorporation of 7 5% of the <lose to the volley in dry soil, before the transplant and 25% in the period of cotton point )showed the best quality miller. The results indicate that the nitrogen incorporation favors to the yield of rice in shelL However the levels of utilities and profitability was similar among the treatments with nitrogen incorporation to the witness exception To.